The Influence of Inquiry Learning on The Environment Care Character of Elementary School Students - Nasution, Putri Jayanti; Widodo, Ari (International Conference on Elementary Education, 2021)
The results of observations that have been in grade 5 on science subjects are the lack of use of models and media in science learning activities by teachers, lack of student participation or activeness in the science learning process, lack of inculcation of character values in science learning. This study aims to determine the process of learning inquiry on the environment care character of grade 5 students in the science concept and to determine whether there is an effect of inquiry learning on student environmental care character. The subjects of this study were students in grades 5A and 5B. This research uses experimental research methods. Based on the results of research in the learning process regarding the use of inquiry learning in science subjects, it is known that inquiry learning can affect the emergence of student the environment care character which can be seen from the post-test results of the experimental class with an average value of 75,38 which is superior to the control class average value is 45,38. From the observations of the experimental class after the application of the inquiry learning obtained an average of 84,46 which is superior to the control class with an average of 72,46. The results of these studies are based on the application of inquiry learning. With inquiry learning, students can more easily understand the material provided, are more active in the learning process, and can develop a caring character for the environment.